Perspectives on the entangled history of communism and Nazism : a comnaz analysis - Karlsson, Klas-Göran; Stenfeldt, Johan, 1978-; Zander, Ulf (Lexington Books, 2015)
"This collection explores the questions of whether, how, and why the histories of German Nazism and Soviet Communism could and should be situated within a single coherent narrative. The contributors examine ideology, terror, secular religion, museum exhibits, and denial in order to critically analyze these complex, entangled historical phenomena"--